Robotics total knee arthroplasty: is an image-based the only solution? - El Motassime, Alessandro; Fulli, Lorenzo; Andriollo, Luca; Ciatti, Corrado; Sangaletti, Rudy; Benazzo, Francesco; Rossi, Stefano Marco Paolo (Frontiers in Surgery, 2026)
Robotic-assisted total knee arthroplasty (TKA) significantly enhances surgical precision and alignment accuracy. While traditional robotic systems rely on preoperative imaging, imageless technology has emerged as a viable alternative, leading to a reduction in costs, radiation exposure, and logistical challenges. This narrative review aims to evaluate the efficacy and reliability of imageless robotic-assisted TKA, specifically assessing its accuracy in component positioning, functional outcomes, and potential advantages over image-based systems. A review of current literature was conducted, comparing imageless robotic TKA with both manual and image-based techniques. The key parameters analyzed include alignment precision, joint line restoration, patient-reported outcomes, and complication rates. Notably, imageless robotic-assisted TKA demonstrated alignment accuracy and functional outcomes comparable to those of image-based systems, while providing enhancements in workflow efficiency and the elimination of radiation exposure. Although a moderate learning curve was observed, no significant differences in patient satisfaction or clinical performance were recorded. Overall, imageless robotic-assisted TKA represents a safe and effective alternative to image-based systems, achieving comparable surgical precision with additional economic and practical benefits. Further research is required to confirm long-term outcomes and to optimize intraoperative guidance strategies.